PENGARUH HADIS RIWAYAT BI AL-MA’NA DALAM PELAKSANAAN HUKUM ISLAM - Zailani Zailani (Jurnal An-Nur, 2015)
Traditions that we encounter now recorded neatly by mukharrij its individual, but when we examine the authenticity of a tradition that exists in the book, there are issues that are very important to note that the process of transformation of the Prophet to the Companions, or of the Companions to the transmitters thereunder before the tradition was recorded, whether in his narration with lafaz, or with meaning. Although the majority of scholars allow the transmission of bi al-ma'na with strict requirements, but it will affect the legal aspects generated by these traditions, because each lafaz used in an Arabic phrase, meaning that the content must have differ- different.